Sense of Place pada Kampung Sunda Sindang Barang sebagai Daya Tarik Obyek Wisata - Nurul Rahma Rasendriya Dwi Aileendra; Defrianto Mandala Nomleni; Helma Julia Lestari; Leonardo Fransisco Purba (Fakultas Teknik - Universitas Bung Karno, 2023)
Sindang Barang Bogor Cultural Village is a tourist attraction that highlights local cultural values and environmental potential. From architectural studies, the existence of this tourist attraction makes sense of place a superior strength. This research is intended to test the sustainability of this potential from SWOT analysis as a strategy for increasing the value of tourist attractions and further development. The research method used is qualitative to explore the elements of sense of place that exist in the area by referring to the existing theoretical framework. From the research results it is known that the design of sense of place was carried out in three ways, namely, transforming the shape of the Sundanese village in building mass concept, creating a space experience by making it a place to stay or stay, including placement between open spaces, shared spaces and residential spaces as activity spaces or accommodating traditional activities, and creating social interactions with the surrounding environment through visits and presence. field space as a socio-cultural space.